THE PROFILE OF FIFTH-GRADE STUDENTS’ SCIENCE PROCESS SKILLS AT MIN IN PONTIANAK CITY - Setyaningrum, Vidya; Anisa, Anisa; Sapipah, Ani Satu; Agustin, Ayu Sarah; Sandy, Utin Putri (Sanata Dharma University Yogyakarta, 2024)
Science process skills are one of the important skills for elementary children because they can provide a solid foundation for scientific understanding, the development of critical thinking skills, and the development of useful abilities throughout life. This research aimed to outline the science process skills profile of fifth-grade students at all Madrasah Ibtidaiyah Negeri (MIN) in Pontianak City. The research used the descriptive method with a quantitative approach. The population of this research is all fifth-grade students of MIN in Pontianak City. The sampling technique used is Stratified Random Sampling, in which 2 classes are taken as samples randomly from each school. Data were collected using multiple choice test instruments, as well as interviews to collect data on the types of errors that cause low science process skills of students. The results of the study showed that the average student’s science process skills only reached 62.3% of each aspect tested. Thus the overall KPS of students at MIN Pontianak City is in the moderate category with an average of 7.2%. Based on the study's findings, it can be concluded that additional efforts are necessary to enhance the science process skills of elementary school students.